A preliminary trial of an online dissonance-based eating disorder intervention. (December 2018) - Green, M.A.; Kroska, A.; Herrick, A.; Bryant, B.; Sage, E.; Miles, L.; Ravet, M.; Powers, M.; Whitegoat, W.; Linkhart, R.; King, B.
Abstract: Objective: We conducted a controlled randomized preliminary trial of an expanded online version of the Body Project ( n  = 46) compared to an assessment-only control condition ( n  = 36) via a longitudinal design (baseline, postintervention, 2-month follow-up) in a community sample of women ( N  = 82) with clinical ( n  = 53) and subclinical ( n  = 29) eating disorder symptoms. Method: The traditional content of the Body Project was modified to include verbal, written, and behavioral exercises designed to dissuade objectification and maladaptive social comparison and adapted to an online format. Body dissatisfaction, self-esteem, self-objectification, thin-ideal internalization, maladaptive social comparison, trait anxiety, positive affect, negative affect, and eating disorder symptomatology were evaluated in the control and the online expanded Body Project condition at baseline, postintervention, and 2-month follow-up. Results: A 2 (condition: online expanded Body Project, control) × 3 (time: baseline, postintervention, 2-month follow-up) mixed factorial multivariate analysis of variance (MANOVA) was conducted to examine statistically significant group differences. As predicted, results indicated a statistically significant condition × time interaction. Conclusions: Participants in the expanded online Body Project condition showed significant reductions in eating disorder symptoms and several associated psychological risk correlates from baseline to postintervention and follow-up; contrary to predictions, eating disorder symptoms and risk correlates were not significantly lower in the online expanded Body Project condition compared to the waitlist control condition at postintervention or 2-month follow-up. Highlights: Results of this preliminary trial suggest an online dissonance-based program may be effective in reducing eating disorder symptoms; Findings suggest the online program effectively reduces eating disorder symptoms from baseline to postintervention and follow-up.